SEBARAN POPULASI, PERSENTASE SERANGAN, DAN TINGKAT KERUSAKAN AKIBAT HAMA BOKTOR PADA TANAMAN SENGON: PENGARUH UMUR, DIAMETER, DAN TINGGI POHON Population Distribution, Damage Percentage, and Damage Level due to Boktor in Sengon: Effect of Age, Diameter... - Asep Hendra Supriatna; Noor Farikhah Haneda; Imam Wahyudi (Jurnal Silvikultur Tropika, 2017)
One of the most important pest that attacks sengon stands is boktor (Xystrocera festiva). Boktor attacks tree stem and causing high damage in term of biological, physiological and economical side. The aim of this study was to analyze damage percentage and damage level on sengon stand in terms of age, diameter and height. The result shows that boktor is starting to attack when the sengon stands are 3 years old with damage percentage and damage level were 20.26 % and 13.32%, respectively. It increased along with the increasing of age, diameter, and height. The highest percentage of damage and level of damage found in 5 years old of sengon stand i.e. 53.71% and 38.07%, respectively. The enhancement of percentage and level of damage caused by the abundant source of food, insect behavior and pest management. Boktor mostly attacks sengon stands in the range of 15.5-18.5 cm in diameter (frequency = 30 trees/ha) and 18.5-21.5 m (frequency = 40 trees/ha) in total height.Key words: boktor, damage percentage, damage level, sengon, tree age